Designing a Web-based Application Mockup for the Registration of Undergraduate Students at Mercu Buana University - Noorly, Akasyah Savina; Ahmad, Rijalul Awal; Ardana, Muhammad Arsy (Journal Collabits, 2025)
New student registration is one of the critical administrative processes in higher education institutions. In the current digital era, web-based systems offer greater practicality compared to the traditional methods, which are often slow and prone to errors. However, many existing systems focus solely on collecting registration data, neglecting the ongoing informational needs of students’ post-registration. This study proposes the design of a web-based registration system that not only facilitates the registration process but also integrates essential features for broadcasting orientation schedules, campus announcements, and other critical information within a single platform. The design incorporates real-time notifications, user-friendly dashboards, and strong data protection measures to enhance user experience and security. Using the waterfall methodology, the study progresses through problem identification, requirements analysis, system design, and prototype evaluation. The resulting prototype, developed using Figma, is tailored to meet the needs of new students and improve campus administrative efficiency. Evaluation results demonstrate that the proposed system effectively bridges gaps in both registration processes and student information management.